THE FUTURE PROSPECTIVE OF GENOMIC BIOTECHNOLOGY IN ANIMAL BREEDING: THEIR POTENTIAL FOR LIVESTOCK PRODUCTION IN PAKISTAN - A. Wajid; T. Hussain; M. Wasim; M. E. Babar; A. A. Anjum; S. A. Shah; K. Abbas; M. M. Manzoor; Noor Badshah (Journal of Animal and Plant Sciences, 2013)
This review paper discusses the exciting scientific and technical advances in genomic biotechnologies which covers a wide range of high throughput techniques for the genetic improvement in animal and livestock production. Advances in molecular genetics and in high throughput technologies for genotyping and sequencing now facilitate the integration of molecular data in genetic improvement programs for livestock on a more comprehensive basis. Moreover, these methods enable a change from using markers on a within family basis for detection and selection on quantitative trait loci (QTL) to using markers that are linkage disequilibrium across the population. Biotechnology has been directed primarily towards reproductive technology have been employed for genetic improvement of farm animals which is foremost concern over the years for scientist and researchers. Transgenesis and cloning are expected to have a significant impact on the future genetic improvement of livestock. This review also described the most recently developed technologies such as GeneChip technology and Next generation high throughput DNA sequencing techniques are opening the fascinating opportunities, provides efficient access to genetic information and enables us to detect functional genes and markers of important traits to facilitate molecular breeding. Particularly every developed and developing countries are engaged in molecular biological activities. The productivity in animal agriculture in Pakistan will need to be significantly increased using these recent genomic and biotechnological methods with the intention of satisfy increasing consumer demand, to more efficiently exploit scarce resources and to generate income for growing agriculture population. Interdisciplinary cooperation will also be needed among industries, consumers and research institution.
Keywords: Genomic biotechnology; Quantitative trait loci; GeneChip technology; Next generation DNA sequencing; Pakistan